Serendipita indica promotes P acquisition and growth in tea seedlings under P deficit conditions by increasing cytokinins and indoleacetic acid and phosphate transporter gene expression - Rong, Zi-Yi; Lei, An-Qi; Wu, Qiang-Sheng; Srivastava, Anoop Kumar; Hashem, Abeer; Abd_Allah, Elsayed Fathi; Kuča, Kamil; Yang, Tianyuan (Frontiers in Plant Science, 2023)
The culturable endophytic fungus Serendipita indica has many beneficial effects on plants, but whether and how it affects physiological activities and phosphorus (P) acquisition of tea seedlings at low P levels is unclear. The objective of this study was to analyze the effects of inoculation with S. indica on growth, gas exchange, chlorophyll fluorescence, auxins, cytokinins, P levels, and expressions of two phosphate transporter (PT) genes in leaves of tea (Camellia sinensis L. cv. Fudingdabaicha) seedlings grown at 0.5 μM (P0.5) and 50 μM (P50) P levels. Sixteen weeks after the inoculation, S. indica colonized roots of tea seedlings, with root fungal colonization rates reaching 62.18% and 81.34% at P0.5 and P50 levels, respectively. Although plant growth behavior, leaf gas exchange, chlorophyll values, nitrogen balance index, and chlorophyll fluorescence parameters of tea seedlings were suppressed at P0.5 versus P50 levels, inoculation of S. indica mitigated the negative effects to some extent, along with more prominent promotion at P0.5 levels. S. indica inoculation significantly increased leaf P and indoleacetic acid concentrations at P0.5 and P50 levels and leaf isopentenyladenine, dihydrozeatin, and transzeatin concentrations at P0.5 levels, coupled with the reduction of indolebutyric acid at P50 levels. Inoculation of S. indica up-regulated the relative expression of leaf CsPT1 at P0.5 and P50 levels and CsPT4 at P0.5 levels. It is concluded that S. indica promoted P acquisition and growth in tea seedlings under P deficit conditions by increasing cytokinins and indoleacetic acid and CsPT1 and CsPT4 expression.